LGRs in Skeletal Tissues: An Emerging Role for Wnt‐Associated Adult Stem Cell Markers in Bone. (3rd July 2020) - Doherty, Laura; Sanjay, Archana
ABSTRACT: Leucine‐rich repeat‐containing G protein‐coupled receptors (LGRs) are adult stem cell markers that have been described across various stem cell niches, and expression of LGRs and their corresponding ligands (R‐spondins) has now been reported in multiple bone‐specific cell types. The skeleton harbors elusive somatic stem cell populations that are exceedingly compartment‐specific and under tight regulation from various signaling pathways. Skeletal progenitors give rise to multiple tissues during development and during regenerative processes of bone, requiring postnatal endochondral and intramembranous ossification. The relevance of LGRs and the LGR/R‐spondin ligand interaction in bone and tooth biology is becoming increasingly appreciated. LGRs may define specific stem cell and progenitor populations and their behavior during both development and regeneration, and their role as Wnt‐associated receptors with specific ligands poses these proteins as unique therapeutic targets via potential R‐spondin agonism. This review seeks to outline the current literature on LGRs in the context of bone and its associated tissues, and points to key future directions for studying the functional role of LGRs and ligands in skeletal biology. © 2020 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.